Truncal Distribution of Fat Mass, Metabolic Profile and Hypothalamic-Pituitary Adrenal Axis Activity in Prepubertal Obese Children - Barat, Pascal; Gayard-Cros, Michelle; Andrew, Ruth; Corcuff, Jean-Benoît; Jouret, Béatrice; Barthe, Nicole; Perez, Paul; Germain, Christine; Tauber, Maïthé; Walker, Brian R.; Mormede, Pierre; Duclos, Martine (The Journal of pediatrics, 2007)
To investigate whether truncal distribution of fat mass (TDFM) is associated with variations of the hypothalamic-pituitary-adrenocortical (HPA) axis activity in prepubertal obese children. TDFM, assessed with dual energy X-ray absorptiometry and a comprehensive set of measures of HPA axis activity and reactivity have been studied in 45 prepubertal obese children aged 6 to 11 years (girls) and 6 to 13 years (boys). After adjustment for whole body fat mass (%) (WBFM), TDFM correlated positively with insulin (r = 0.50, 95% CI [0.23; 0.70]) and homeostasis model assessment of insulin resistance (r = 0.52, 95% CI [0.25; 0.71]). When adjusted for WBFM, TDFM correlated positively with morning plasma cortisol (r = 0.38, 95% CI [0.15; 0.64]) in the total population. TDFM correlated negatively with the rise of salivary cortisol after a standard meal (r = −0.43, 95% CI [−0.71; −0.02]), obviously in girls. When adjusted for WBFM and TDFM, morning plasma cortisol correlated positively with total cholesterol (r = 0.41, 95% CI [0.11; 0.65]) and triglyceride (r = 0.44, 95% CI [0.14; 0.67]). The rise of salivary cortisol after a standard meal was negatively (r = −0.56, 95% CI [−0.85; −0.01]) and positively (r = 0.74, 95% CI [0.16; 0.94]) correlated with homeostasis model assessment of insulin resistance in boys and girls, respectively. Association exists in prepubertal obese children between TDFM and markers of HPA axis activity. These data suggest that HPA axis could be involved early in life in obesity associated with pejorative metabolic profile.